Iron ore sintering part 2. quality indices and productivity (2014)
Sinter plants have to process mineral mixes in order to obtain sinter of a suitable composition and quality to be loaded into the blast furnace. For this purpose a series of parameters need to be taken into account, such as the nature and composition of each component of the mineral mix and the conditions of the manufacturing process. Sinter is subjected to in-depth characterisation in terms of chemical and granulometric analysis, determination of the mineral phases in its structure and of quality indices such as reducibility, low temperature degradation, reduction degradation, and tumbler strength. It is also important to operate sinter plants with high productivity and to ensure a uniform sinter composition and quality so as to facilitate the steady state operation of the blast furnace.